2012
DOI: 10.1143/apex.5.025201
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Plasmonic Nanodiscs by Photonic Nanojet Lithography

Abstract: In this study, we present and demonstrate a new route to the fabrication of plasmonic nanostructures with a controlled size and shape using photonic nanojet lithography. Through the approach of dual-layer lift-off, the achievable size was remarkably reduced to a sub-100 nm scale and the introduction of an engineered diffuser was proved to give a facile and precise way of controlling the anisotropy in shape without a process burden even when the spherical focusing beads are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 16 publications
(18 reference statements)
0
25
0
Order By: Relevance
“…• Synthesis of the Precursor: ZAD (1.8 g, 7.7×10 -3 mol) was treated with an equimolar 29,30 amount of EA (0.47 mL). The mixture was kept at 60 °C under continuous stirring for 24 h.…”
Section: Samples Preparationmentioning
confidence: 99%
“…• Synthesis of the Precursor: ZAD (1.8 g, 7.7×10 -3 mol) was treated with an equimolar 29,30 amount of EA (0.47 mL). The mixture was kept at 60 °C under continuous stirring for 24 h.…”
Section: Samples Preparationmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11]. ZnO thin films can also be used in nanobiotechnological applications [12].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Upon illuminating a micron-sized lossless dielectric microcylinder or microsphere with plane wave light, a propagating light beam that is narrow and bright, and can propagate over a distance longer than the wavelength, can be obtained from the shadow-side surface of the microcylinder or microsphere. Various types of application based on the PNJ have been proposed and demonstrated, such as spectroscopy with high sensitivity 2,3,8) and optical lithography for the fabrication of ultrafine structures.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of application based on the PNJ have been proposed and demonstrated, such as spectroscopy with high sensitivity 2,3,8) and optical lithography for the fabrication of ultrafine structures. 4,5,6,11) Moreover, Kong et al reported that the propagation length of the PNJ could be increased by incorporating a multilayered graded-index structure in the microcylinder or the microsphere. 7) This suggests that designing an appropriately nonuniform distribution of dielectric permittivity in the microcylinder or microsphere can be effective to obtain a PNJ with a higher performance.…”
Section: Introductionmentioning
confidence: 99%